The Effect Of Green Accounting And Green Banking On Company Value With GCG as A Moderating Variable (Empirical Study on Banking Companies for the Period 2021-2023) - Franco Benony Limba; Theresia Febiengry Sitanala; Adonia Anita Batkunde; Dewi Nidia Soepriadi; Alfrin Ernest Marthin Usmany (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of Green Accounting and Green Banking on Company Value, with Good Corporate Governance (GCG) as a moderating variable, in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. This research is motivated by the increasing attention to sustainability practices in the financial sector and the need to ensure that environmentally friendly policies can provide added economic value to companies. The research method used is a quantitative approach with moderated regression analysis. Secondary data were obtained from annual reports and banking sustainability reports during the study period. The results show that Green Accounting has a positive and significant effect on Company Value. Conversely, Green Banking has a positive but insignificant effect on Company Value. Furthermore, the moderating role of GCG on the relationship between Green Accounting and Company Value is proven to be positive but insignificant. Meanwhile, GCG significantly moderates the relationship between Green Banking and Company Value, but with a negative direction. This study emphasizes the importance of integrating sustainability policies and corporate governance so that positive signals sent through environmentally friendly practices can be translated into increased company value.